Analisis Kebugaran Jasmani Siswa Sekolah Dasar dan Menengah di Kecamatan Golewa - Bile, Robertus Lili; Tapo, Yohanes Bayo Ola; Dopo, Fransiskus Solanus (Jurnal Porkes, 2025)
This study aims to evaluate the physical fitness levels of elementary and middle school students in Golewa District. This quantitative cross-sectional study involved a population of 547 students from 5 schools. A sample of 222 students was selected purposively. The measurement instrument used was the Indonesian Student Fitness Test (TKSI). Data analysis techniques were analyzed descriptively using SPSS 25 and TKSI standard norms. The results of the fitness study did not increase linearly with age. Phases A (grades 1-2 elementary school) and C (grades 5-6 elementary school) showed a good category (scores of 3.96 and 3.92), while phases B (grades 3-4 elementary school), D (junior high school), and EF (senior high school) were in the sufficient category (scores of 3.4, 3.58, and 3.54). Cardiovascular endurance declined consistently to the poor category (2.7) in high school, while muscle strength remained relatively stable. The results show a fluctuating pattern of fitness development. Fitness was relatively high in the early phase (grades 1–2) and late elementary school (grades 5–6), but declined in the middle of elementary school (grades 3–4) and remained consistently low in junior high and high school. The component that declined the most was cardiovascular endurance, while muscle strength remained relatively stable in all phases. It was concluded that fitness development is fluctuating and is determined more by the quality of learning and consistency of physical activity than by age alone.